2005
DOI: 10.1016/j.accreview.2004.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Single versus multiple internal mammary artery grafting for coronary artery bypass: 15-year follow-up of a clinical practice trial

Abstract: Background-The long-term clinical advantages of using routine multiple internal mammary artery (IMA) grafts for coronary artery bypass (CAB) are not clear. This study was designed to test the hypothesis that multiple IMA grafts would provide better 15-year outcomes when compared with single IMA and vein grafts. Methods and Results- Between 1984Between and 1987Between , 1067 consecutive patients undergoing isolated CAB were referred to 1 surgeon practicing primarily single and another surgeon maximizing mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 9 publications
0
37
1
Order By: Relevance
“…However, survival curves do not separate until several years postoperatively, which has been a consistent finding [15, 88, 89; Figure]. The demonstrated clinical advantages of BIMA grafting strategies include prolonged survival and reduced need for coronary reintervention on the basis of recurrent myocardial ischemia, including freedom from the need for coronary reintervention [15,88,90] which hold true for women as well as for men, where it has been demonstrated that use of BIMA had 3-fold improved cardiacrelated survival compared with patients who did not receive an IMA graft [91]. Reported rates of BIMA use in CABG range from 4.0% to nearly 50% depending upon several factors including the contributing authors' practice preferences and the particular patient cohort treated [19][20][21][22]92].…”
Section: Bilateral Internal Mammary Artery Conduitsmentioning
confidence: 88%
See 2 more Smart Citations
“…However, survival curves do not separate until several years postoperatively, which has been a consistent finding [15, 88, 89; Figure]. The demonstrated clinical advantages of BIMA grafting strategies include prolonged survival and reduced need for coronary reintervention on the basis of recurrent myocardial ischemia, including freedom from the need for coronary reintervention [15,88,90] which hold true for women as well as for men, where it has been demonstrated that use of BIMA had 3-fold improved cardiacrelated survival compared with patients who did not receive an IMA graft [91]. Reported rates of BIMA use in CABG range from 4.0% to nearly 50% depending upon several factors including the contributing authors' practice preferences and the particular patient cohort treated [19][20][21][22]92].…”
Section: Bilateral Internal Mammary Artery Conduitsmentioning
confidence: 88%
“…Most notably, the LIMA-LAD graft has been shown to be an independent predictor of survival after CABG when compared with patients not receiving LIMA-LAD [76]. In addition, using more than one IMA graft reduces the need for subsequent reintervention and prolongs survival relative to patients receiving only one arterial grafts www.intechopen.com [15,17]. Similarly, Guru et al evaluated the potential benefit of multiple arterial grafting in over 53,000 patients undergoing primary CABG between 1991 and 2001.…”
Section: General Advantages Of Arterial Graftingmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recent studies reported better outcomes after use of BITA grafts, especially in the younger population. [1][2][3][4][5] However, some studies reported higher rates of surgical site infection (SSI) after use of BITA grafts because of the decreased blood supply to the sternum and surrounding tissues. [6][7][8] Previous studies investigating the feasibility of using BITA grafts in elderly patients included patients aged >65 or >70 years, [9][10][11][12] but the feasibility of using BITA grafts specifically in octogenarians has not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Such a benefit seems more evident in young patients, but it cannot be ruled out that those other groups of less favorable prognostic can get advantages of this surgical strategy [9]. DM is long recognized as an important risk factor for infection and dehiscence of surgical wound [10]; therefore, there is a special concern with diabetic patients.…”
Section: Introductionmentioning
confidence: 99%